Multi-center clinical study of Parkon® efficiency - Fjodorova NE; Shtok VH; Gusev EI; Naum Goldstein (Open Journal of Parkinson's Disease and Treatment - Peertechz Publications, 2021)
The purpose of the study was to investigate the efficacy of Parkon® spray as the compound for the effect on motor disturbances in treatment of both Parkinson's Disease (PD) and neuroleptic-induced Parkinsonism. The main active ingredient of Parkon® is low concentrated hydrogen peroxide [1-3].